Exploring the bacterial community and fermentation characteristics during silage fermentation of abandoned fresh tea leaves. (November 2021) - Lin, Haiyu; Lin, Shiqi; Awasthi, Mukesh Kumar; Wang, Yuefei; Xu, Ping
Abstract: The potential application of silage fermentation on abandoned fresh tea leaves (AFTL) was investigated. Dynamic profiles of fermentation-related components, characteristic components and the bacterial community of AFTL during ensiling were analysed. The results showed that after ensiling for 60 days, the concentrations of lactic, acetic and propionic acid increased, whereas a high pH value (4.80) and NH3 –N content (106 g/kg TN) were detected. Characteristic components, including caffeine, polyphenols, theanine and catechins, were well preserved. The microbial community changed significantly, and Lactobacillus (63.6%) became the dominant phylum. Spearman rank correlation revealed a positive correlation between lactic acid concentration and the abundance of Lactobacillus (63.6%) and Klebsiella (25.0%), whereas the abundance of Klebsiella was negatively correlated with catechin concentration. In conclusion, ensiling could be an effective utilization for AFTL and provides a new idea for utilizing idle resources on tea plantations. Graphical abstract: Image 1 Highlights: Silage fermentation was employed to utilize the abandoned fresh tea leaves. The health-promoting chemicals in tea leaves were well preserved during ensiling. Lactic acid was positively correlated with the abundance of Lactobacillus and Klebsiella. The abundance of Klebsiella was negatively correlated with catechins.